Combinatorial commutative algebra - Miller Ezra; Sturmfels Bernd (New York Springer-Verlag, 2005)
Combinatorial commutative algebra is an active area of research with thriving connections to other fields of pure and applied mathematics. This book provides a self-contained introduction to the subject, with an emphasis on combinatorial techniques for m
Keywords: Combinatorics; Commutative algebra